International Reserve Adequacy in the Gambia - Tereanu, Eugen (IMF Working Papers; Working Paper ;, 2010)
This paper applies intertemporal models of precautionary saving to compute an optimal level of international reserves for The Gambia. The analysis focuses on current account shocks specific to a low-income economy with a significant import component and complements a more standard, rule-of-thumb reserve adequacy assessment. The results suggest a central range from 4.5 months to 7 months of imports, which is broadly aligned with the recent actual coverage. Notwithstanding parameter sensitivity, the simulations allow for more informed policy decisions that balance flexibility with a prudent approach to reserve use.